2023
DOI: 10.1007/s13300-022-01355-4
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus Recommendations on Time in Range for Monitoring Glucose Levels in People with Diabetes: An Indian Perspective

Abstract: Keeping up with the global scenario, diabetes prevalence is on rise in India. Inadequate glycemic control is a major cause of diabetes-related morbidity and mortality. The conventional standards of care (SOC) in diabetes, including self-monitoring of blood glucose and measurement of glycated hemoglobin, have supported achievement of glycemic control, yet there are a few limitations. With the use of current technologies and metrics, such as continuous glucose monitoring (CGM) and standardized CGM data reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In addition to the improvement in ADG, in the present study the FDC treatment also led to significant changes in TIT, which increased from 40.73±28.62% to 54.77±34.24% (overall improvement of 34.47%, p<0.05). The study results compliments the goal set by the ADA, which includes the description of and the use of CGM report as part of its standard of care (SOC) since 2020 [20]. According to the ADA, a TIT of glucose level between 70 to 180 mg/dL should be greater than 70% [28] For patients below 25 years of age, the TIT should be >60 % and for older patients, >50% TIT is recommended.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition to the improvement in ADG, in the present study the FDC treatment also led to significant changes in TIT, which increased from 40.73±28.62% to 54.77±34.24% (overall improvement of 34.47%, p<0.05). The study results compliments the goal set by the ADA, which includes the description of and the use of CGM report as part of its standard of care (SOC) since 2020 [20]. According to the ADA, a TIT of glucose level between 70 to 180 mg/dL should be greater than 70% [28] For patients below 25 years of age, the TIT should be >60 % and for older patients, >50% TIT is recommended.…”
Section: Discussionmentioning
confidence: 58%
“…For the Indian population, it has been demonstrated that a TIT of more than 70% correlates to an HbA1c level of less than 7.5%. [20]. The increase in the TIT while reducing the TBT is considered the primary glycaemic goal to achieve effective and safe glucose control [21].…”
Section: Discussionmentioning
confidence: 99%
“…Poor glycaemic control in pregnancy can have detrimental consequences not only for the mother but also for the developing foetus[ 16 ]. Therefore, CGM emerges as a protective tool for achieving favourable obstetric outcomes in pregnancies complicated by T1DM[ 17 ]. Studies have shown that pregnant women using CGM exhibit improved glycaemic control.…”
Section: Cgm Effect On Pregnancy and Neonatal Outcomesmentioning
confidence: 99%
“…In South Asia, especially India, CGMs are predominantly used for diabetes evaluation. 17 While wellness and lifestyle monitoring apps enjoy reasonable following, the data include user-uploaded, non-biomarker information such as food logs, step counts, sleep duration, etc., which provide a general overview of health but cannot be substantially correlated to clinical biomarkers. This gap in biomarker-based tracking is especially crucial for India which is increasingly being known as the "Diabetic capital of the world".…”
Section: Introductionmentioning
confidence: 99%